Evaluation of the CD123 Expression and FLT3 Gene Mutations in Patients with Acute Myeloid Leukemia - Freidoon Solhjoo; Akbar Safaie; Ahmad Monabati; Maral Mokhtari; Moeinadin Safavi (Iranian Society of Pathology, 2018)
Background and Objective: Identification of cytogenetic and molecular changes plays an important role in acute myeloid leukemia (AML) patients. Thus, they are used in classification, prognosis and treatment of the disease. The CD123 expression and FLT3 gene mutations are also the variations that may assist in prognosis and treatment of patients with AML.Methods: This study was performed on 76 patients as new cases of AML. The correlation between CD123 immunohistochemical (IHC) expression and FLT3 gene mutations with each other as well as morphological, immunophenotypical and cytogenetic factors was studied.Results: The results represented the CD123 IHC expression in 55.3% and FLT3 gene mutations in 28.9% of cases. We found that 81.3% of patients who had FLT3/ITD gene mutations revealed IHC of CD123 expression (P=0.019). The CD123 expression against FLT3 was also correlated with monocytic differentiation in bone marrow blasts (P=0.031). There were significant correlations between IHC expression of CD123 and FLT3/ITD mutations with a high percentage of aspirated bone marrow blasts (P=0.01 and P=0.006, respectively) as well as the lack of CD34 expression in bone marrow blasts (P=0.007 and P=0.021, respectively).Conclusion: The CD123 IHC positive AMLs were correlated with certain pathologic features, some of which can be similar with correlations of background mutation of FLT3/ITD; According to the negative predictive value (NPV), 88.2% of CD123 IHC showed FLT3 gene mutation. In addition to its use in targeted therapy, it could be a marker to decide what molecular tests to use in the next steps.